Regulasi Vaksinasi Covid-19 pada Sektor Pariwisata di Kota Semarang: Perspektif Hukum Administrasi Negara - Paradhiva, Rr. Moza Adzani (Kertha Patrika; Vol 46 No 3 (2024)DO - 10.24843/KP.2024.v46.i03.p.05, 2024)
The Covid-19 outbreak has resulted in significant losses across various sectors, notably the tourism sector, which is recognized as a Priority Sector for Job Development under President Joko Widodo's administration. In response, the government implemented health and vaccination protocols to mitigate the spread of Covid-19 and gradually revive the tourism industry. This research aims to examine the rights and obligations of stakeholders concerning the regulations governing health and vaccination protocols for the tourism sector in Semarang City. The data for this study were obtained through a literature review, employing descriptive qualitative methods. The author utilized both a statutory approach and a conceptual approach to gather information. This research will specifically analyze the framework of health and vaccination protocol regulations during Covid-19 pandemic in Indonesia, focusing on the tourism sector from the perspective of State Administrative Law. In this analysis, the author applies the Principles of Formulating Good Legislation and the General Principles of Good Governance (AUPB), emphasizing the need for legal certainty for stakeholders in the tourism sector. The findings indicate that the regulations established in Semarang City between 2020 and 2021 primarily revolved around activity restrictions and health protocols. While there is a delineation of rights and obligations among stakeholders regarding the enforcement of health protocols, there remains a lack of legal clarity concerning rights and responsibilities related to vaccination in the tourism sector. Consequently, rights such as access to health insurance and the ability to engage in economic activities within the tourism industry have not been fully established.